Analysis of the first temperate broad host range brucellaphage (BiPBO1) isolated from B. inopinata - Jens Andre Hammerl; Cornelia eGöllner; Sascha eAl Dahouk; Karsten eNöckler; Jochen eReetz; Stefan eHertwig (Frontiers in Microbiology, 2016)
Brucella species are important human and animal pathogens. Though, only little is known about mobile genetic elements of these highly pathogenic bacteria. To date, neither plasmids nor temperate phages have been described in brucellae. We analysed genomic sequences of various reference and type strains and identified a number of putative prophages residing within the Brucella chromosomes. By induction, phage BiPBO1 was isolated from B. inopinata. BiPBO1 is a siphovirus that infects several Brucella species including B. abortus and B. melitensis. Integration of the phage genome occurs adjacent to a tRNA gene in chromosome 1 (chr 1). The bacterial (attB) and phage (attP) attachment sites comprise an identical sequence of 46 bp. This sequence exists in many Brucella and Ochrobactrum species. The BiPBO1 genome is composed of a 46,877 bp double-stranded DNA. Eighty-seven putative gene products were determined, of which 32 could be functionally assigned. Strongest similarities were found to a temperate phage residing in the chromosome of Ochrobactrum anthropi ATCC 49188 and to prophages identified in several families belonging to the order rhizobiales. The data suggest that horizontal gene transfer may occur between Brucella and Ochrobactrum and underpin the close relationship of these environmental and pathogenic bacteria.